PENGARUH REKRUTMEN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA HOTEL GRAND ZURI PEKANBARU - Lola Kori Lofika Lumban Raja; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims t determine the effect of recruitment and compensation on employee performance partially and simultaneously. This study uses questiomaires as a means of collecting data distributed 87 employees in Hotel Grand Zuri Pekanbaru. The data from the questiomaireswas further processed using descriptive analysis and statistical analysis, using SPSS 18.0 by performing validity test, reliability test, simple linear analysis, multiple linear analysis, determination analysis (R2) and hyphotesis test with t test (partial) and F(simultaneous).The result showed that the result of the first hyphotesis testing of recruitment employee performance is t hitung (8.795) >ttabel (1.988), meaning that recruitment variables significantly effect employee performance. Both compensation on employee performance is thitung (10.175) >ttabel (1.988), meaning compentation has a significantly effect on employee performance. The result of F test of recruitment and compensation on employee performance is Fhitung (85.001) >Ftabel (3.105), meaning recruitment and compensation simultaneously have a significant effect on employee performance.Keywords: Recruitment, Compensation, Employee Performance